2010
DOI: 10.1073/pnas.1010740107
|View full text |Cite
|
Sign up to set email alerts
|

Reiterative AP2a activity controls sequential steps in the neural crest gene regulatory network

Abstract: The neural crest (NC) emerges from combinatorial inductive events occurring within its progenitor domain, the neural border (NB). Several transcription factors act early at the NB, but the initiating molecular events remain elusive. Recent data from basal vertebrates suggest that ap2 might have been critical for NC emergence; however, the role of AP2 factors at the NB remains unclear. We show here that AP2a initiates NB patterning and is sufficient to elicit a NB-like pattern in neuralized ectoderm. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
187
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(203 citation statements)
references
References 33 publications
(57 reference statements)
15
187
1
Order By: Relevance
“…16 However, both direct Wnt/b-Catenin target genes, tfap2a and gbx2, are already expressed at that stage and in the case of tfap2a this early expression also depends on BMP signaling. 30,32,38 Moreover, tfap2a induction in na€ ıve ectodermal explants required only low levels of Wnt/ b-Catenin activity, 30 suggesting that low endogenous activity is sufficient to induce tfap2a in the NPB. During gastrulation, NPB genes apparently exhibit differential sensitivity toward Wnt/b-Catenin signaling.…”
Section: Wnt Signalingmentioning
confidence: 99%
See 4 more Smart Citations
“…16 However, both direct Wnt/b-Catenin target genes, tfap2a and gbx2, are already expressed at that stage and in the case of tfap2a this early expression also depends on BMP signaling. 30,32,38 Moreover, tfap2a induction in na€ ıve ectodermal explants required only low levels of Wnt/ b-Catenin activity, 30 suggesting that low endogenous activity is sufficient to induce tfap2a in the NPB. During gastrulation, NPB genes apparently exhibit differential sensitivity toward Wnt/b-Catenin signaling.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…27,29 The transcription factor AP2-alpha (gene: tfap2a) is considered as the central player in NPB specification. 30 In blastula and early gastrula stage Xenopus embryos, tfap2a is expressed in the entire non-neural ectoderm and the prospective NPB territory and a recent study showed that this expression depends on BMP activity. 31,32 The source of BMP ligands is likely the non-neural ectoderm or the prospective NPB ectoderm itself, which expresses BMP ligands in zebrafish, frog, chick and mouse embryos.…”
Section: Bmp Signalingmentioning
confidence: 99%
See 3 more Smart Citations